Developing successful business strategies : gaining the competitive advantage - Reider, Rob, 1940- (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2015)
This book presents effective planning of business strategies and related budgeting concepts, and those activities necessary for the successful growth of the organization. The planning process is shown to be an integral function of developing management strategies for future growth and the gaining of competitive advantage in these fast moving times. Budgeting is presented as a logical outgrowth and an essential part of the planning process rather than an independent internal activity. The book emphasizes the principal factors that should be considered in planning and budgeting for the company, what management and operations personnel must know to better understand effective planning for the business, and what can be done to enhance the overall strategic and financial planning for the organization.
Internal operational planning considerations -- Strategic (long-range) planning -- The short-term operating plan -- Budgeting and profit planning -- Management reporting and control -- About the author -- Other books by Rob Reider -- Index.
Part of: 2014 digital library.
Includes index.
Title from PDF title page (viewed on December 21, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Strategic planning; Business planning; budgeting; business models; competitive advantage; detail planning; external analysis; forecasting; front-end strategy analysis; internal analysis; long- term planning; organizational planning systems; planning; short-term planning; situational analysis; strategic planning; strategies; strategy development; Electronic books